Espacios expositivos virtuales: Proyecto UMUSEO, una nueva opción para la difusión artística. - Francisco Javier Caballero Cano (Virtual Archaeology Review)
The technology revolution has, in recent years, meant something of a transformation in the way we perceive art and, at the same time, in our way of understanding art exhibition spaces. New works demand updated spaces and different approaches to their care and exhibition. American museums were the first to respond to these changes and begin to put resources behind the necessary objectives. Throughout the 1980s a revolutionary process unfolded which focused on changing attitudes and opening up to a growing and increasingly diverse audience. This process soon spread to the rest of the world and gradually museums and exhibition spaces started to become part of an overall impulse of opening-up and conceptual change that, judging by the outcomes, was precisely what society was waiting and asking for. Rather than change their collections, museums changed their interpretation of them, the way in which they were brought to their publics, their approach to external communications and the role of visitors. New information technologies (particularly the most recent) offer museums the chance to respond to society’s requirements. Hence access to museums takes on a whole new dimension. As well as the traditional uses of the Internet, art online offers two new possibilities: interactivity and the removal of physical barriers. Museums online are open to anybody and everybody, at any time of day, offering easy access and the scope for users to relate directly with a virtual exhibition space. The emergence of the Internet has transcended the barriers of space and time, enabling real-time communication with people from all continents, meaning that messages can be conveyed with limitless reach. The University of Murcia´s Virtual Museum project – UMUSEO – makes an innovative contribution to the possibilities offered by new technologies in the realm of artistic production and its dissemination. This is a research project designed to be a Centre for a range of art-forms operating exclusively online and specialising in exhibitions relating to the artistic heritage of the University of Murcia. In the 1960s and 70s questions started to be asked about the role of museums and their future, giving rise to the idea that museums had become passive exhibition centres. Today they are continually evolving, becoming centres of active experimentation in which public participation takes on a special relevance.